1. Epileptic seizures in pediatric stroke: Data from the Italian Registry for Childhood Thrombosis. Issue 1 (January 2015) - Baggio, L.; Sartori, S.; Nosadini, M.; Gentilomo, C.; Saracco, P.; Agostini, M.; Bassi, B.; Palmieri, A.; Laverda, A.M.; Simioni, P.; Suppiej, A.; per il G.I.R.T.I. (Gruppo Italiano Registro Trombosi Infantili)
<x xml:space="preserve">Abstract</x> According to data from the Italian Registry for Childhood Thrombosis (R.I.T.I.), in about half cases diagnosis of pediatric stroke occurs after 24 h from clinical onset (Baggio et al., SINP2013). The aim of the present study was to evaluate the frequency of seizures at stroke onset and their correlation with time to diagnosis in the pediatric stroke patients in the R.I.T.I. We selected the R.I.T.I. children with first acute arterial (AIS) or venous (CSVT) cerebral infarction occurring between January 2007 and June 2012; we studied prevalence, characteristics and recurrence of epileptic seizures, focusing on diagnostic delay. At stroke onset, epileptic seizures occurred in 27.27% of the 63 AIS, and in 50% of the 14 CSVT. In the AIS patients with seizures at stroke onset, diagnosis occurred within 6 h in 30.77%, while in only 12.82% of the seizure-free patients. In the CSVT patients with seizures at stroke onset, diagnosis occurred within 6 h in 28.57%, while in only 14.28% of the seizure-free patients. At discharge, relapse of seizures occurred in 28.57% AIS and in 16.67% CSVT groups. Epileptic seizures are common at onset of stroke in childhood, and they correlate with a more timely diagnosis.